Alginate hydrogel-coated syringe needles for rapid haemostasis of vessel and viscera puncture. (August 2020) - Ren, Jingli; Yin, Xingjie; Chen, Yu; Chen, Yu; Su, Hua; Wang, Ke; Zhang, Lianbin; Zhu, Jintao; Zhang, Chun
Abstract: Tissue puncture is an effective means in the diagnosis and treatment of diseases, providing important information for clinical doctors. Yet, haemorrhage is still a main and unavoidable complication, which can cause serious outcomes, especially in patients with abnormal coagulation function. Herein, we present a facile yet effective strategy to prepare haemostatic needles by coating the syringe needles surface with alginate-CaCl2 -based hydrogel with carefully optimized mechanical and chemical properties, which can effectively prevent bleeding following tissue puncture. The needle with haemostatic coating exhibits complete prevention of blood loss following vessel and viscera puncture in the normal animal as well as in animal models with hemorrhagic diathesis. The syringe needle with haemostatic coating in this work holds enormous potentials for clinical applications, including sampling and injection. Graphical abstract: Haemostatic needles are prepared by coating syringe needles with partially cross-linked Alginate-CaCl2 hydrogel and with carefully optimized mechanical strength, which can swell during a puncturing process and physically seal the puncture wounds. The haemostatic hydrogel coating exhibited good biocompatibility and can be gradually dissociated without influencing the normal physiological function of the tissues as well as the healing of the wound sites. The needle with haemostatic coating shows complete prevention of blood loss following blood vessel and viscera puncture including in normal and haemorrhage model. Image 1